Glial heterotopia presenting as nasal polyp - Report of two cases (Bangladesh Journal of Medical Science, 2013)
This report described two cases of nasal glial heterotopia which primarily presented as nasal polyp. Glial heterotopia one form of congenital midline nasal mass is a rare anomaly usually detected at birth. There are congenital malformation of displaced normal, mature glial tissue, which is no longer in continuity with an intracranial component. The case reports correlates clinical findings with immunohistochemical investigations. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13360 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.104-107